Evidência empírica dos factores explicativos dos dividendos distribuídos pelas empresas cotadas na EURONEXT Lisboa - Ribeiro, Alexandrino (2012)
Companies’ decision to pay dividends to its shareholders is a topic that has received increasing attention in business finance. This paper provides an additional contribution to the development of this topic focusing on the analysis of the determinants of dividend policy by issuing companies in the Portuguese capital market. For this purpose, we use a set of financial and economic information specific to each firm to explain its dividend per share. The sample used in the empirical study contains 54 firms and it refers to the 2005-2009 period. Results suggest that net income, dividends per share paid in the previous financial year and return on assets all present a positive and statistically significant effect on dividends per share paid in a given financial year. Moreover, results show that Lintner’s (1956) model appears to be valid in explaining dividend policy by issuing companies in Euronext Lisbon.